Légal protection of consumer goods and services in their électronique contractas - Laouamri, Walid (Journal of Human Sciences, 2021)
Legal protections for the satisfaction of consumers of goods and services in their electronic contracts have become the focus of legal thought with its three dimensions of legislation, jurisprudence and justice. This protection is based on the poor status of consumers and the imbalance between them and between those who provide goods or services to market and sell them via electronic media.